Multiwalled carbon nanotubes for combination therapy: a biodistribution and efficacy pilot study. Issue 16 (25th March 2019) - Biagiotti, Giacomo; Pisaneschi, Federica; Gammon, Seth T.; Machetti, Fabrizio; Ligi, Maria Cristina; Giambastiani, Giuliano; Tuci, Giulia; Powell, Emily; Piwnica-Worms, Helen; Pranzini, Erica; Paoli, Paolo; Cicchi, Stefano; et al.
Abstract : A doxorubicin/metformin carrier for chemotherapy based on oxidized MWCNTs. Efficacy in vitro and in vivo . Abstract : A drug delivery system (DDS) for combined therapy, based on a short oxidized multiwalled carbon nanotube, is reported. It was prepared by exploiting a synthetic approach which allowed loading of two drugs, doxorubicin and metformin, the targeting agent biotin and a radiolabeling tag, to enable labeling with Ga-68 or Cu-64 in order to perform an extensive biodistribution study by PET/CT. The DDS biodistribution profile changes with different administration methods. Once administered at therapeutic doses, the DDS showed a marginal beneficial effect on 4T1 tumor bearing mice, a syngeneic and orthotopic model of triple negative breast cancer, with survival extended by 1 week and 2 days in 20% of the mice. This is encouraging given the aggressiveness of the 4T1 tumor. Furthermore, our DDS was well tolerated, ruling out concerns regarding the toxicity of carbon nanotubes.